Effects of Diet Induced Weight Reduction on Cartilage Pathology and Inflammatory Mediators in the Joint Tissues - Sun, Antonia RuJia (Front Med (Lausanne), 2021)
Obesogenic diets contribute to the pathology of osteoarthritis (OA) by altering systemic and local metabolic inflammation. Yet, it remains unclear how quickly and reproducibly the body responds to weight loss strategies and improve OA. In this study we tested whether switching obese diet to a normal chow diet can mitigate the detrimental effects of inflammatory pathways that contribute to OA pathology. Male C57BL/6 mice were first fed with obesogenic diet (high fat diet) and switched to normal chow diet (obese diet → normal diet) or continued obese diet or normal diet throughout the experiment. A mouse model of OA was induced by surgical destabilization of the medial meniscus (DMM) model into the knee joint. Outcome measures included changes in metabolic factors such as glucose, insulin, lipid, and serum cytokines levels. Inflammation in synovial biopsies was scored and inflammation was determined using FACs sorted macrophages. Cartilage degeneration was monitored using histopathology. Our results indicate, dietary switching (obese diet → normal diet) reduced body weight and restored metabolic parameters and showed less synovial tissue inflammation. Systemic blood concentrations of pro-inflammatory cytokines IL-1α, IL-6, IL-12p40, and IL-17 were decreased, and anti-inflammatory cytokines IL-4 and IL-13 were increased in dietary switch group compared to mice that were fed with obesogenic diet continuously. Although obese diet worsens the cartilage degeneration in DMM OA model, weight loss induced by dietary switch does not promote the histopathological changes of OA during this study period. Collectively, these data demonstrate that switching obesogenic diet to normal improved metabolic syndrome symptoms and can modulate both systemic and synovium inflammation levels.